Cytokines in uveitis. Issue 3 (May 2018) - Weinstein, Jessica E.; Pepple, Kathryn L.
Abstract : Purpose of review: Increasing evidence supports Th17 cells as key mediators of ocular inflammatory disease. Cytokines that are important for the development and pathologic function of these cells are potential therapeutic targets in patients with immune mediated uveitis. This review provides an overview of these cytokines including recent insights about their roles in ocular inflammation from laboratory and clinical studies. Recent findings: Interleukin (IL)-6, IL-10, IL-17, IL-22, IL-23 and tumour necrosis factor-alpha (TNFα) are cytokines that have been examined for their functional role in uveitis and their relationship to pathologic Th17 cells. Studies in animal models, particularly in experimental autoimmune uveitis (EAU), have been instrumental in studying the role of these cytokines in disease pathogenesis. More recently, studies on aqueous, vitreous and serum from patients with uveitis using flow cytometry and multiplex ELISA bead-based methodologies have provided insights into the contribution of Th17 cells and the related cytokines in ocular inflammatory diseases. The central role of IL-23 in determining the pathologic Th17 fate has made it an effective therapeutic target in systemic diseases such as psoriasis and thereby an attractive potential target for patients with immune-mediated uveitis. Summary: Th17 cells, and their related cytokines, are important inflammatory mediators in autoimmune uveitis. Animal and human studies continue to provide new information to direct development of new cytokine-targeted therapies for patients with uveitis.